Essays on international trade - Mariano, Lucas de Castro (2024)
This paper investigates the effects of Brazil’s 1990s trade liberalization on dropout rates from higher education. Since the trade shock had strong effects on the labor market, it could also have affected educational decisions. Using a shift-share instrument combining tariff cuts and employment across industries in a region to measure local economy exposure to the trade shock, we find that regions more exposed to the exogenous tariff cuts experienced a permanent relative increase in dropout rates of 7 percent even 20 years after the trade reform. Computing different regional tariff shock measures for adult and young workers, we find that the net effect is mainly explained by the impact on adult workers. This suggests that the income effect more than offsets the substitution effect in determining the impact of tariff cuts. This paper examines the impact of Brazil’s 1991 trade liberalization on intergenerational mobility (IGM). To measure the local economy’s exposure to the trade shock, we employ a shift-share instrument that combines tariff cuts and employment across industries within a region. Our findings indicate that regions with higher exposure to the exogenous tariff reductions experienced a permanent relative decline in upward occupational mobility and a long-term decrease in both absolute income and relative educational mobility compared to regions with less pronounced effects. Additionally, we analyze IGM measures separately for son-father and daughter-mother pairs to account for gender heterogeneity, where daughters suffer higher reductions in income and educational mobility. We find that the overall effect is primarily driven by negative consequences in the labor market, characterized by an increase in the proportion of low-skilled occupations and a decrease in earnings levels following the trade shock. Rural-to-urban migration has been an issue that has been raised with the structural transformation of developing countries transitioning from rural to urban activities. In this paper, we aim to explore the effects of the China trade shock in Brazil on the share of people living in slums. Brazil’s trade with China predominantly involves exporting agricultural and extractive goods, while the growth in imports was concentrated in manufactures. We leverage this unique context and construct two measures of exposition to trade, one local and the other at the origin of migrants. We find that local exposition to import competition is correlated with reductions in the population living in slums, and export demand at the origin reinforces this effect, deterring migrants from moving from rural to urban areas.